Analysis of the role of village apparatus in management accountability of the lembang revenue and expenditure budget (APBL) - Ade Lisa Matasik; Dorce Lapik; Luther P. Tangdialla (Enrichment : Journal of Management, 2023)
Objectives from the study This is a for-know role device village in accountability management budget income and spending lembang (APBL) in Lembang Roroan Barra'-Barra' District deadlock. This research provides an overview of how to prepare a budget in a clear and detailed manner. The type of study used is descriptive-qualitative by doing observation, interviews, and documentation. Informant in the study This totals 8 people who are device village in Lembang Roroan Barra'-Barra', i.e., head Lembang, secretary Lembang, Kaur finance, man general and planning, head sexy government, chief sexy well-being, chief sexy service, and heads hamlet. Results of research conducted show that device village in Lembang Roroan Barra'-Barra' has a role in a manner that is good and appropriate with regulations and applicable laws.